484 Early Orthopaedic Input in Trauma Patients During COVID Times And Its Importance in The Post-COVID Era. (4th May 2021) - Saleem, S; Parikh, S; Loeffler, M
Abstract: The Pandemic made way for interdepartmental collaborative efforts to action an early orthopaedic review of all trauma patients bypassing AnE, during the COVID pandemic. Retrospective, single centre collection of data including 55 wrist and 40 ankle injuries that presented to the hospital in the month of January and April, marking pre-COVID and COVID times respectively. Data was gathered under following parameters: 1-Number of hospital visits, 2-Number of fracture clinic appointments, 3-Number of admissions and 4- Time to definite management. Simple data analysis was done to calculate means of all the parameters. The average time to definite Management for distal radius fractures dropped from 2.78 to 0.86 days. For the same cases a dip in number of hospital visits was noted, from 2.72 to 2.09. Mean admissions for these patients dropped from 0.12 to 0.09. The results quiet evidently show that early orthopaedic input reduced hospital visits, hospital admissions and time to definite management for distal radius fracture cases. A decrease in patient exposure to the hospital translates to reduced chance of contracting the COVID-19 virus. These results can prove very useful in setting guidelines, as we navigate patient care in uncertain COVID times.